Revitalisasi Bisnis di Era Digital: Peranan Media Sosial dalam Mengembangkan Komunikasi Bisnis: Literature Review - Mia Nurmiarani; Farida Hariyati; Olih Solihin; Efendi Agus Waluyo (Universitas 45 Surabaya, 2023)
In the dynamic digital era, businesses face significant challenges and opportunities that demand a revitalization of strategies to keep up with technological advancements and consumer dynamics. The aim of this research is to delve deeper and further investigate the role of social media in developing business communication in the digital age. This study employs a literature review approach as the foundation for gathering discussion materials. The research findings indicate that the use of social media in the context of business communication is not only relevant but also crucial for success and business development in the digital era. Its presence not only influences aspects of online business development but also serves as a key factor in strengthening corporate communication, fostering business collaboration, and adapting to crisis conditions. In conclusion, the use of social media in business communication development in the digital era has a significant impact on businesses.